2008
DOI: 10.1111/j.1440-1746.2008.05413.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among total colonoscopic findings, clinical symptoms, and laboratory markers in ulcerative colitis

Abstract: In this study, clinical symptoms reflected the activity of distal colonic lesions, whereas CRP and ESR reflected the activity of proximal lesions. Therefore, total colonoscopy may be indicated when CRP or ESR is elevated in UC patients in clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 24 publications
4
53
1
1
Order By: Relevance
“…Patients having an active colitis, UCa (n ¼ 15), or an inactive colitis UCi (n ¼ 13) were classified according to Sandborn's histological activity scale. 20 Patient details are given in Supplementary Tables S1-S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients having an active colitis, UCa (n ¼ 15), or an inactive colitis UCi (n ¼ 13) were classified according to Sandborn's histological activity scale. 20 Patient details are given in Supplementary Tables S1-S2.…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory activity, as stated in the pathology report, was evaluated blindly by an experienced gastroenterologist who did not have access to glycan expression or clinical data and graded according to Sandborn's histological activity scale (0-4). 20 Sandborn score 0-1 is regarded as inactive disease with no presence of neutrophils, but level 1 has hypercellular lamina propria. Score 2-4 is regarded as active disease with infiltration of neutrophils, cryptitis, and crypt abscesses of increasing degree.…”
Section: Patient Data and Collection Of Colonic Biopsiesmentioning
confidence: 99%
“…The histopathological scoring system used in this study is primarily focused on the changes in the infiltration of polymorphonuclear (PMN) cells into the surface epithelium, the crypts, and in the lamina propria. It correlates well to endoscopic and clinical scores and is regarded as an additional independent variable [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the correlation of blood biomarkers and these endoscopic indices. In 2008, Osada et al [2] scored the endoscopic activity in seven colonic segments (appendiceal region, cecum, ascending colon, transverse colon, descending colon, sigmoid colon, and rectum) by use of the Mayo Endoscopic Score, comparing endoscopic activity with blood biomarkers. They reported that CRP and ESR correlated well with proximal rather than distal colonic activity, suggesting that total colonoscopy is needed in cases of elevated CRP or ESR among UC patients in clinical remission [2].…”
mentioning
confidence: 99%
“…In 2008, Osada et al [2] scored the endoscopic activity in seven colonic segments (appendiceal region, cecum, ascending colon, transverse colon, descending colon, sigmoid colon, and rectum) by use of the Mayo Endoscopic Score, comparing endoscopic activity with blood biomarkers. They reported that CRP and ESR correlated well with proximal rather than distal colonic activity, suggesting that total colonoscopy is needed in cases of elevated CRP or ESR among UC patients in clinical remission [2]. Karoui et al [3] also reported a significant correlation between CRP and the Rachmilewitz Endoscopic Index (r = 0.46, P \ 0.0001) in a prospective study of 101 UC patients.…”
mentioning
confidence: 99%